2017
DOI: 10.1111/roie.12322
|View full text |Cite
|
Sign up to set email alerts
|

Employment gains from minimum‐wage hikes under perfect competition: A simple general‐equilibrium analysis

Abstract: Contrary to conventional wisdom, higher minimum wages may lead to greater levels of employment under perfect competition. We demonstrate this possibility in a simple general-equilibrium model of involuntary unemployment, with two goods produced by two factors and consumed by two representative households. Within our model, hiking a minimum wage redistributes income between heterogeneous consumers. This redistribution may create an excess demand for the labor-intensive good, and hence increase total employment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Card and Krueger (1993, 1995) empirically study the employment of the fast‐food industry in New Jersey and Pennsylvania and they find that employment increases with the minimum wage rate. Similar results are derived in Ahn, Arcidiacono, and Wessels (2003), Aaronson and French (2007), Brecher and Gross (2018), and Marjit, Ganguly, and Acharyya (2021). For example, Marjit et al (2021) derives this positive relationship between the minimum wage and employment using the same framework proposed by Gruen and Corden (1970).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Card and Krueger (1993, 1995) empirically study the employment of the fast‐food industry in New Jersey and Pennsylvania and they find that employment increases with the minimum wage rate. Similar results are derived in Ahn, Arcidiacono, and Wessels (2003), Aaronson and French (2007), Brecher and Gross (2018), and Marjit, Ganguly, and Acharyya (2021). For example, Marjit et al (2021) derives this positive relationship between the minimum wage and employment using the same framework proposed by Gruen and Corden (1970).…”
Section: Introductionsupporting
confidence: 85%
“…However, the changes of prices are wrongly anticipated within the search models. In order to explain this result, many supplementary attributes are gradually introduced into traditional models, such as monopsony, heterogeneous consumers and the complementary relation (see Aaronson & French, 2007; Brecher & Gross, 2018). Distinguished from the existing theoretical literature, the discussion of this part provides a new mechanism that can be a potential explanation of the relationship between the minimum wage and unemployment.…”
Section: Discussion On the Minimum Wagementioning
confidence: 99%
“…Burdett and Mortensen (1998) find higher levels of employment along with increasing minimum wages when the labor market is characterized by monopsonistic competition with search activities. Under heterogeneous consumers, Brecher and Gross (2018) obtain a positive effect of minimum wages on employment via income redistribution, which can yield higher demand for labor-intensive goods. Neumark et al (2013) find that, by controlling spatial heterogeneity, there are in general no reductions in employment from minimum wage regulations but employment is lowered for teenagers.…”
mentioning
confidence: 99%
“…recent work suggests that a relative consensus on the effects of the minimum wage on employment came undone". Some authors, such as Brecher and Gross [5], have identified (theoretical) conditions under which "within a simple general-equilibrium model of perfect competition, higher minimum wages may paradoxically lead to greater levels of total employment". They introduced heterogeneous households with specific propensities to consume, using a two goods model.…”
Section: Literature Reviewmentioning
confidence: 99%